PENDAMPINGAN PENGELOLAAN SAMPAH BERBASIS KOMUNITAS POSYANDU KARTINIKELURAHAN NGALIYAN - KOTA SEMARANG (Faculty of Social Science, Universitas Negeri Semarang, 2015)
The objectives of this empowerment to the strengthening of environmental awareness according to the principles of conservation to provide guidance to residents of RT 13 / RW 06 Sub Ngaliyan through knowledge transfer include matters related to the management and processing of kitchen waste, increase the participation of community members, and strengthening to the community as a pioneer of environmental care. Activity methods consistent measures of community assistance through: socialization, practice, and mentoring as well as to monitor the success of the activities. Kitchen waste separation has been carried out by members of the community according to type, namely: assortment of vegetables, plastic, leftover food and other waste disposed in the trash that has been owned by each member. Participatory members in environmental management in accordance prinsi-conservation principles were shared by all (100%) members, this condition is relatively easy to do because of the community living in housing that is built. The practice of processing kitchen waste into compost is done by three teams consisting of 5-7 family. Results compost is used to fertilize ornamental plants and to fertilize plants roadside South Karonsih. Indicators of success are known activities of enthusiastic participants in the discussion that demonstrate mastery of the material. In addition it is nevertheless manage and process waste even without assistance.